Optimizing the implementation of safe and sustainable by design to better enable sustainable innovation - Ramya Rajagopal; Florence Bohnes; Predrag Kukic; Giles Rigarlsford; Evita Vandenbossche-Goddard; Bruno Campos; Claire Davies; Ian Malcomber; Gavin Maxwell; Sarah Sim (iScience)
Summary: The concept of safe and sustainable by design (SSbD) combines considerations of human safety, environmental safety, and sustainability. The SSbD framework developed by the European Commission’s (EC) Joint Research Centre (JRC) and the Safe(r) and Sustainable Innovation Approach (SSIA) developed by the Organisation for Economic Co-operation and Development (OECD) are two key examples of how SSbD concepts could be implemented in future regulatory frameworks. SSbD assessment can greatly aid the innovation process to ensure that new chemicals/materials, processes, and products are safe and sustainable throughout the life cycle. Unilever is a global consumer goods company that integrates the latest safety and sustainability science and SSbD principles in the innovation process. In this work, we review the JRC SSbD framework and OECD SSIA, taking into consideration the reflections of stakeholders through a review of published and gray literature, to evaluate to what extent they enable SSbD innovation. We make recommendations on how current gaps and challenges can be addressed to enable maximal uptake by all stakeholders across the value chain. The recommendations are mainly aimed at ensuring that the JRC SSbD framework and OECD SSIA are conceptually robust and addressing the practical elements in the use of the latest scientific methodology, availability of data, tools, guidance, and a standardized approach to interpreting results and decision-making, through short- and longer term efforts.